Probabilistic analysis of slab-column connections subjected to punching shear according to the ABNT NBR 6118 (2014) recommendations considering the model error measure - Marque,Náyra Louise Alonso (2021)
abstract: Reinforced concrete flat slabs are structural systems in which slabs are directly supported by columns, without the use of beams. A structural phenomenon that deserves attention in these systems is the punching shear, characterized by the occurrence of shear stresses close to the slab-column interface, which can produce fragile rupture in those regions. This study presents some results of reliability index β obtained for slab-column connections based on FORM, according to the Brazilian standard’s model, considering the model error. The critical contours C and C’ without shear reinforcement are analyzed. The results showed that failure in the C contour is very unlikely, while the probabilities of rupture in the C' contour when considering the influence of the model error are greater than the target values recommended in the literature for the ULS.